Micro-Macro Interactions in Ethno-Religious Homogamy among Hui Muslims in Contemporary China: The Roles of Residential Concentration and Aging. Issue 1 (2nd January 2016) - Mu, Zheng; Lai, Qing
Abstract: Chinese Muslims have actively maintained religious endogamy. However, no research has assessed the role of local residential context in individual Muslims' marital choices, nor have sociologists examined the heterogeneity in individual Muslims' responses to such contextual influences. Using Chinese census data between 2000 and 2005, this paper offers a first investigation of such micro–macro interactions among the Hui, the largest Muslim ethnic group in China. Specifically, we test the effect of the Hui's residential concentration (at the prefecture level) on individual Hui's marital choices (exogamy/endogamy/singleness) and how this effect varies by gender and age. Several major findings emerge from our multilevel discrete-time competing-risk models, highlighting the impact of contextual factors, but also a level of individual resilience against aggregate-level cultural forces. While at younger ages, Hui can still afford to wait to contract an endogamous marriage; with aging, they started to choose exogamy to fulfill the expectation of universal marriage.